2014
DOI: 10.1371/journal.pone.0089783
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial Capacity of Aedes aegypti: Effects of Temperature and Implications for Global Dengue Epidemic Potential

Abstract: Dengue is a mosquito-borne viral disease that occurs mainly in the tropics and subtropics but has a high potential to spread to new areas. Dengue infections are climate sensitive, so it is important to better understand how changing climate factors affect the potential for geographic spread and future dengue epidemics. Vectorial capacity (VC) describes a vector's propensity to transmit dengue taking into account human, virus, and vector interactions. VC is highly temperature dependent, but most dengue models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
399
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(447 citation statements)
references
References 31 publications
17
399
1
5
Order By: Relevance
“…Carrington et al, in a study conducted in northwest Thailand have found that large diurnal temperature range (DTR) adversely affects mosquito biology by extending immature development phase, lowered larval survival and reduced female reproductive capacity (Carrington et al, 2013a). Our findings of mosquito abundance and DTR reinforce these findings along with those from a diversity of laboratory studies demonstrating the effects of DTR (Lambrechts et al, 2011;Carrington et al, 2013b;Carrington et al, 2013c;Liu-Helmersson et al, 2014;Murdock et al, 2017) on a variety of mosquito life history traits like survival, fecundity, larval development, biting rates, vector competence, and viral transmissions.…”
Section: Discussionsupporting
confidence: 86%
“…Carrington et al, in a study conducted in northwest Thailand have found that large diurnal temperature range (DTR) adversely affects mosquito biology by extending immature development phase, lowered larval survival and reduced female reproductive capacity (Carrington et al, 2013a). Our findings of mosquito abundance and DTR reinforce these findings along with those from a diversity of laboratory studies demonstrating the effects of DTR (Lambrechts et al, 2011;Carrington et al, 2013b;Carrington et al, 2013c;Liu-Helmersson et al, 2014;Murdock et al, 2017) on a variety of mosquito life history traits like survival, fecundity, larval development, biting rates, vector competence, and viral transmissions.…”
Section: Discussionsupporting
confidence: 86%
“…aegypti and Ae. albopictus [71,72], ability to transmit dengue in relation to temperature and diurnal temperature variability. We found strong temperature dependent dengue epidemic potential, with optimal transmission around a constant temperature of 29⁰C, with vectorial capacity decreasing at higher temperatures.…”
Section: Specific Objectivesmentioning
confidence: 99%
“…We found strong temperature dependent dengue epidemic potential, with optimal transmission around a constant temperature of 29⁰C, with vectorial capacity decreasing at higher temperatures. This decline was partly offset when diurnal temperature range was larger, with at least part of the day reaching near-optimal conditions [71,72]. Incorporating these findings using historical and predicted temperature and DTR over 200 years (1901–2099), there was an increasing trend in dengue epidemic potential in temperate regions.…”
Section: Specific Objectivesmentioning
confidence: 99%
“…Liu-Helmersson and colleagues have pointed to the importance of diurnal temperature range in the dengue epidemic potential [61]. Many previous studies have focused only on the mean temperature values.…”
Section: Surveillance and Warning Systemsmentioning
confidence: 99%